2020
DOI: 10.1177/0271678x20964233
|View full text |Cite
|
Sign up to set email alerts
|

Age-related impairment of cerebral blood flow response to KATP channel opener in Alzheimer’s disease mice with presenilin-1 mutation

Abstract: Local cerebral blood flow (CBF) responses to neuronal activity are essential for cognition and impaired CBF responses occur in Alzheimer’s disease (AD). In this study, regional CBF (rCBF) responses to the KATP channel opener diazoxide were investigated in 3xTgAD, WT and mutant Presenilin 1(PS1M146V) mice from three age groups using Laser-Doppler flowmetry. The rCBF response was reduced early in young 3xTgAD mice and almost absent in old 3xTgAD mice, up to 30%–40% reduction with altered CBF velocity and mean ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…A preserved brain vascular supply is required to ensure the delivery of enough glucose and oxygen to support information processing and cognition. In neurodegenerative diseases, the aging-related impairment of K ATP channels and NO-signaling pathways, neurovascular uncoupling, and pericyte process rarefaction and decrease in capillary density are further exacerbated (3840). In this study, we report preserved neuronal activity in aged brains upon WP stimulation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preserved brain vascular supply is required to ensure the delivery of enough glucose and oxygen to support information processing and cognition. In neurodegenerative diseases, the aging-related impairment of K ATP channels and NO-signaling pathways, neurovascular uncoupling, and pericyte process rarefaction and decrease in capillary density are further exacerbated (3840). In this study, we report preserved neuronal activity in aged brains upon WP stimulation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In patients, isocapnic hypoxia opens K ATP channels and causes an increase in the CBF, thereby maintaining oxygen delivery and brain partial O 2 (46). With age, the increase in CBF produced by K ATP channel opening is reduced, and this is further aggravated at an early stage of AD and likely caused by reduced expression of K ATP channels (38). Long-term treatment of AD mice at an early stage with K ATP channel opener improves cognitive function and reduces the tau and amyloid burden (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, LRP1 mediated vascular clearance of Aβ from the brain 49 ; hence, abnormal vascular function might induce cerebral hemodynamic dysregulation and further aggregate Aβ deposition. Previous studies have reported that microvascular lesions altered Aβ plaques 50 ; local cerebral blood flow responses to neuronal activity were impaired in AD 51 ; and neurovascular dysregulation even occurred in middle‐aged APOE ‐ε4 carriers. 52 Nevertheless, aerobic exercise significantly improved hippocampal blood flow in hypertensive APOE ‐ε4 carriers, which might be beneficial for individuals at high risk of AD.…”
Section: Discussionmentioning
confidence: 95%
“…Intriguingly, current investigations suggest that activation of the KATP channel significantly contributes to cerebrovasodilation and plays a pivotal role in autoregulation both of which are impaired in the context of TBI (Pastor et al, 2019). Furthermore, emerging evidence confirms that blockage of KATP channel is closely associated with cognitive impairment (Liu et al, 2021;Moriguchi et al, 2021). These findings raise questions that nicorandil may represent a promising approach for ameliorating cognitive impairment after TBI.…”
Section: Introductionmentioning
confidence: 90%